Thermally conductive composites with hydroxylated boron nitrides for the efficient thermal management of superconducting coils. (15th November 2021) - Kim, Jun Min; Song, Seunghyun; Hwang, Young Jin; Jang, Jae Young; Lee, Sanggil; Shin, Dong-In; Lee, Sung Woo; Jeong, Sooyeol; Kim, Seung-Hyun; Yi, Gi-Ra; Choi, Yeon Suk; Lee, Gaehang
Abstract: The thermal conductivity (κ) of polymer nanocomposites with boron nitride (BN) nanoplates is critically dependent on the distribution of BN in the polymer matrix. Here, we heavily functionalized BN nanoplates with hydroxyl groups by ultrasonication in solution with boric acid. Then, the hydroxylated BN nanoplates could be homogeneously distributed in an epoxy matrix, which improved the through-plane κ of 2.09 and 1.96 W/m·K at 25 and -90 °C, respectively. Processable composite resin with hydroxylated BN was utilized as an adhesive for a low-temperature superconducting (LTS) coil to enhance its normal zone propagation velocity (NZPV) and cooling rate performance. Consequently, fast heat dissipation through the adhesive between superconductors contributed to a 65.8% of increase in NZPV and a 13.1% improvement in the cooling rate of the device compared with a commercial adhesive. Graphical abstract: Image 1 Highlights: A BN edge was selectively functionalized using boric acid. Functionalization was done at the sub-kilogram scale. The higher affinity of b -BN to the epoxy enhanced the κ value of the composite. The high κ improved NZPV and cooling rate of the superconducting coil.